IMPROVEMENT OF STATE ARCHIVES ACTIVITY IN THE REPUBLIC OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
The development of archiving in Uzbekistan during the years of independence is one of the poorly researched topics. The article reveals positive changes in archiving on the basis of sources and available literature. In particular, issues such as the formation of the National Archival Fund, strengthening the material and technical base of archives, the introduction of modern information technologies into archiving, the acquisition and usage of archival documents, the publishing activities of archival institutions and training of personnel for archives are covered